The People, Place and Space Reader - Michele F. Fontefrancesco (University of Belgrade, 2021)
Jen Jack Gieseking and William Mangold with Cindi Kats, Setha Low, and Susan Saegert (editors). 2014. The People, Place and Space Reader. New York – Oxon: Routledge. 446 + xxxiv pp.  ISBN978-0-415-66497-4